A reliability and validity study of the electronic health literacy scale among stroke patients in China. Issue 3 (3rd April 2023) - He, Yu; Guo, Lina; Zauszniewski, Jaclene A.; Wei, Miao; Zhang, Gege; Lei, Xiaoyu; Liu, Yanjin
ABSTRACT: Background: Patients with stroke usually use smartphones to obtain online information to maintain their health. But their ability to identify, evaluate and apply this information is still unknown. Aim: This study was designed to examine the reliability and validity of the electronic Health Literacy Scale among patients with stroke in China. Design: This is a cross-sectional survey. Methods: A demographic questionnaire, the electronic Health Literacy Scale (e-HLS) and the eHealth Literacy Scale (eHEALS) were administered to a sample of 648 patients with ischemic stroke recruited from December 2020 to March 2021 in a tertiary hospital. Results: The Cronbach'α coefficient on the e-HLS-CHI was 0.907. Kappa consistency coefficient of test-retest reliability was 0.691 ( p < .05). Three factors were extracted by Exploratory Factor Analysis (EFA), accounting for 90.84% of the total variance. Confirmatory Factory Analysis (CFA) revealed that three factors of e-HLS-CHI fit well (NFI = 0.979, RFI = 0.955, IFI = 0.987, TLI = 0.972, CFI = 0.987, RMSEA = 0.070, CMIN/DF = 2.586). Good simultaneous validity was suggested by the positive correlation of 0.94 ( p < .001) between the e-HLS-CHI and eHEALS. When using eHEALS as the standard, the area under the ROC curve of e-HLS-CHI was 0.896 (95% CI: 0.831–0.960, p < .001). The sensitivity and specificity were 97.8% and 70.4% respectively. Conclusions: The e-HLS can be used to evaluate electronic health literacy of patients with stroke in China after translation and cultural adaption.